Spatial Modelling and Analysis of an Electrical Distribution System - Ogunbiyi, O.; Olayinka, A. A.; Ahmed, M. O. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2019)
The distribution of electrical energy to end-users in Nigerian communities is faced with diverse spatial problems leading to low voltage, overload on equipment, difficulties in fault tracing and delay in fault clearing. The traditional management system is not only manual but also has flaws such as difficulties in searching and updating previous records as well as no real-time information on their distribution assets. In this study, a geospatial technique was employed for effective management of the electricity distribution system in Malete, Kwara State, Nigeria. Spatial information of distribution asset was collected from the field and used in the structural modelling of the distribution network in the ArcMap software. Analysis of the model and the available information showed that 80 % of the transformers were not properly located at the centroid of the load. The span of the network fairly conformed to standard as only 45.73 % were within 45-50 m. The result also showed that 40 % of the transformers were overloaded with an unbalanced load, hence the need for restructuring of the network.